PRIVATIZING ENLIGHTENMENT IN THE RE-EMERGENCE OF RELIGION - Wood, Gabrielle M (Journal of Dharma, 2009)
While water is life for the living, true spiritual teachings mean eternal life to those seeking salvation. Spiritual teachings, which show the way to experience spiritual development and enlightenment, become a well from which the seeker can draw truth. Jesus said, “Everyone who drinks this water will be thirsty again, but whoever drinks the water I give him will never thirst. Indeed, the water I give him will become in him a spring of water welling up to eternal life.” Just as water should be available to all who thirst, the timeless spiritual teachings that illuminate religious truths should be available to all who seek. Buddha explained that: “When the Tathagata [“fully enlightened Buddha”] or the Tathagata’s disciples live in the world, it is done for the good of the many, for the happiness of the many, out of compassion for the world-for the good, the welfare and the happiness of gods and men.